Cross-sectional Study on Sero-Prevalence of Porcine Reproductive and Respiratory Syndrome in Bagmati Province of Nepal - Prajapati, Meera; Maharjan, Ayush; Vaal, Sonam (Journal of Nepal Agricultural Research Council, 2024)
A total of 178 samples were collected from four districts of Bagmati provinve from March 2022 to January 2023 and the serum samples were tested for antibodies against PRRS virus by ID Screen® PRRS Indirect Enzyme-linked immunosorbent assay (ELISA) kit. Out of 178 samples, 28 samples were found to be positive for PRRSV antibodies indicating overall prevalence of 15.73% with the highest prevalence observed in Kathmandu (11.79%) and lower prevalence in Lalitpur district (3.93%). Notably, no sero-positive cases were detected in Kavrepalanchowk and Chitwan districts suggesting a localized distribution of PRRSV within the province, potentially influenced by differences in farming practices, biosecurity measures, or animal movement between districts. Age-wise analysis revealed significantly higher sero-prevalence in younger pigs aged 0-6 months (8.42%) and 7-12 months (6.74%) compared to older pigs over 12 months (0.56%). Female pigs exhibited a higher prevalence (10.67%) compared to males (5.05%), although this difference was not statistically significant. Farm management practices significantly impacted on PRRSV prevalence. The incidence of PRRSV infection was found to be more in farms which had relatively poor biosecurity measures and unhygienic environment. Hence, the findings of this study revealed the presence of PRRSV antibodies among pig populations of Bagmati province. For an effective control and prevention, strict biosecurity and quarantine measures along with continuous monitoring of the pig populations is highly important. Farmers should be educated about biosecurity, pig disease transmission and management and quarantine because majority of them are unaware of these issues.